c.2 - Parihar, D R (Igatpuri, 2005)
The main focus of the study was on Central and State Government officials. However, executives, managers, etc. in Public Sector Undertakings and professors, lecturers, etc. in Government Institutes of Higher & Technical Education were also included to make the study more comprehensive.
Keywords: IFS as an author